Acceptance of Telepathology in Daily Practice - Thomas Mairinger (Analytical Cellular Pathology)
The availability of pathology services differs greatly in our environment. Although pathology would be especially suitable for being practised at a distance by transporting digital image information, the spread of telepathology into everyday work still is relatively slow.